2022
DOI: 10.3389/fonc.2022.841262
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Proliferation of Tongue Cancer With Artificial Intelligence in Contrast-Enhanced CT

Abstract: Tongue squamous cell carcinoma (TSCC) is the most common oral malignancy. The proliferation status of tumor cells as indicated with the Ki-67 index has great impact on tumor microenvironment, therapeutic strategy making, and patients’ prognosis. However, the most commonly used method to obtain the proliferation status is through biopsy or surgical immunohistochemical staining. Noninvasive method before operation remains a challenge. Hence, in this study, we aimed to validate a novel method to predict the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…After this screening process, 12 articles were selected, and the data were retrieved, as shown in Table 1 . 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25
Fig. 1 PRISMA flowchart.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After this screening process, 12 articles were selected, and the data were retrieved, as shown in Table 1 . 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25
Fig. 1 PRISMA flowchart.
…”
Section: Resultsmentioning
confidence: 99%
“… Oral cavity images acquired using smartphones Pre-trained CNNs are used for identifying oral pre-cancerous and cancerous lesions and to differentiate them from normal mucosa using a dataset of clinically annotated photographic images Study demonstrated the performance of CNN models in identification and classification comparable to a biopsy report Sun et al. (2022) 17 To validate a novel method to predict the proliferation status of TSCC using contrast-enhanced CT (CECT) based on AI CECT images of the lesion area from 179 TSCC patients Sample analyzed using a CNN Study provided a possibility of predicting the proliferation status of TSCC using AI in CECT noninvasively before operation Warin (2021) 20 To use the CNN deep learning algorithms to develop an automated classification and detection model for oral cancer screening. A total of 700 clinical oral photographs were collected retrospectively from the oral and maxillofacial center, which were divided into 350 images of oral squamous cell carcinoma and 350 images of normal oral mucosa Classification and detection models were created by using DenseNet121 and faster R-CNN, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation